State of the Art: Mechanical Properties of Ultra-High Performance Concrete - Mohamadtaqi Baqersad; Ehsan Amir Sayyafi; Hamid Mortazavi Bak (Salehan Institute of Higher Education, 2017)
During the past decades, there has been an extensive attention in using Ultra-High Performance Concrete (UHPC) in the buildings and infrastructures construction. Due to that, defining comprehensive mechanical properties of UHPC required to design structural members is worthwhile. The main difference of UHPC with the conventional concrete is the very high strength of UHPC, resulting designing elements with less weight and smaller sizes. However, there have been no globally accepted UHPC properties to be implemented in the designing process. Therefore, in the current study, the UHPC mechanical properties such as compressive and tensile strength, modulus of elasticity and development length for designing purposes are provided based on the reviewed literature. According to that, the best-recommended properties of UHPC that can be used in designing of UHPC members are summarized. Finally, different topics for future works and researches on UHPC’s mechanical properties are suggested.